Toward a Configural Theory of Job Demands and Resources - Ong, Wei Jee; Johnson, Michael D. (Academy of Management Journal, 2023)
Job demands-resources research has largely adopted a variable-centered approach to test main and interactive effects of demands and resources on employee outcomes. However, this approach cannot det...